Discharge of the newborn: timing, mode and controls - Vasarri, Pier Luigi (Study of serum leptin in well differentiated thyroid carcinoma: Correlation with patient and tumor characteristics, 2013)
Many of the practices routinely used at birth centers are based more on habits developed through time, rather than the result of true scientific evidence. We have conducted a survey in the birth centers in Tuscany to verify the different care practices for healthy term newborn infants.